High-cohesiveness and high-water-resistance light environment-friendly sound insulation coating and preparation method thereof
By using components such as silicone modified acrylic emulsion and modified bentonite in sound insulation coatings, combined with aerogel dispersed slurry and various microbead fibers, the problem of difficult balance between bond strength, water resistance and sound insulation effect of existing sound insulation coatings is solved, and efficient sound insulation effect and good construction performance are achieved.
Patent Information
- Application Number
- CN202510073691.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-17
AI Technical Summary
Existing sound insulation coatings are difficult to balance between bonding strength, water resistance and sound insulation effect, and most products have problems such as cracking, poor water resistance, long drying time and poor construction performance.
Silicone modified acrylic emulsion is used as film-forming substance, combined with aerogel dispersed slurry, hollow glass microbeads, expanded perlite and wood fibers as sound insulation fillers, and modified bentonite is added to improve bonding, water resistance and sound insulation effect.
It achieves high adhesion, high water resistance and excellent sound insulation, avoids the problems of cracking and long drying time of thick coatings, and improves the durability and construction performance of the coating.
Smart Images

Figure CN119875460A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and mainly relates to a lightweight, environmentally friendly sound-insulating coating with high adhesion and high water resistance and a preparation method thereof. Background Art
[0002] At present, as people's requirements for quality of life increase, residential comfort, as an important indicator of quality of life, has received more and more attention. Noise not only affects residents' rest, study and work, but may also damage hearing health and even cause diseases. There are two ways for noise to propagate in residential buildings. One is air transmission, such as the sound of speaking, telephone, musical instrument playing, etc.; the other is solid transmission, such as the noise caused by floor vibration caused by people walking and moving furniture. Research data on residential noise shows that the main source of noise is the impact sound of building floors, such as footsteps upstairs, the sound of heavy objects falling, and the sound of children running and jumping. Sound insulation pads, rock wool, sound insulation mortar and sound insulation coatings can reduce the impact sound of building floors, but sound insulation pads are flammable and easy to hollow when laid; rock wool is currently restricted for use because it is carcinogenic; the application thickness of sound insulation mortar is large, generally 30mm, which will greatly reduce the indoor space; therefore, sound insulation coatings are more suitable for sound insulation of building floor impact sound.
[0003] At present, all kinds of sound insulation coating products are in the development stage, and the quality varies greatly. Common raw materials for preparing sound insulation coatings include rubber, vermiculite, isocyanate resin, fiber cotton and white sand. However, rubber and isocyanate synthetic resins are not green and environmentally friendly; white sand has a high specific gravity and will increase the load on the coating; vermiculite has low strength and is easy to crack; fiber cotton has poor water resistance, and in order to achieve a good sound insulation effect, the bonding strength of the product is ignored, which is not suitable for large-scale promotion and application.
[0004] In addition, existing sound insulation coating products are prone to cracking or even falling off due to insufficient adhesion when applied thickly; sound insulation coatings have poor water resistance and are prone to fading, cracking and falling off when exposed to moisture for a long time; after the sound insulation coating is applied, the coating takes a long time to dry, affecting the construction efficiency; the sound insulation coating is in poor condition and is prone to stratification and poor storage, which also indirectly affects the construction performance; the sound insulation effect of sound insulation coatings is average and unsatisfactory; the viscosity strength of sound insulation coatings and the sound insulation effect cannot achieve an ideal balance. In order to achieve a sound insulation effect that meets national standards, its bonding strength is generally small, which greatly affects its application.
[0005] In summary, it is necessary to develop a new technical solution to solve the defects and shortcomings in the existing technology. Summary of the invention
[0006] The present invention provides a lightweight and environmentally friendly sound-insulating coating with high adhesion and high water resistance. The coating uses silicone-modified acrylic emulsion as a film-forming substance, and is matched with aerogel dispersion slurry, hollow glass microspheres, expanded perlite and wood fiber as sound-insulating fillers. Modified bentonite is added to increase the compatibility of the components, improve the adhesion, water resistance and sound insulation effect of the coating, and has the characteristics of being lightweight and environmentally friendly, and has good application prospects.
[0007] One object of the present invention is to provide a lightweight environmentally friendly sound insulation coating with high adhesion and high water resistance, wherein the lightweight environmentally friendly sound insulation coating with high adhesion and high water resistance comprises the following components in parts by weight:
[0008]
[0009] The modified bentonite is obtained by reacting acrylate grafted bentonite, silane coupling agent grafted hollow glass microspheres, and eleostearic acid grafted wood fiber;
[0010] The organosilicon-modified acrylic emulsion is obtained by the reaction of organosiloxane, organosilicon coupling agent and acrylate.
[0011] Furthermore, the silicone-modified acrylic emulsion is a silicone-acrylic emulsion with a silicone content of 30-40%, has good adhesion, can firmly adhere to the surface of the substrate, and has excellent water resistance, can effectively prevent moisture penetration, and is flexible and crack-resistant, and can protect the coating from cracking when applied thickly, thereby improving the durability of the coating.
[0012] Furthermore, the aerogel dispersion slurry is a silica aerogel paste prepared by dispersing aerogel powder in water, which has excellent hydrophobic properties and ultra-low density, with a density of 0.4-0.5 g / cm 3 ; High solid content, about 30%, environmentally friendly and dust-free, which can give the material lighter and sound-insulating properties.
[0013] Furthermore, the particle size of the expanded perlite is 2-4 mm.
[0014] Furthermore, the expanded perlite is a closed-cell expanded perlite, which has high flexibility, crack resistance, light weight, and low specific gravity, is conducive to improving construction performance, and has good heat insulation and sound insulation properties.
[0015] Furthermore, the particle size of the hollow glass microspheres is 50-150 μm.
[0016] Furthermore, the chemical composition of the hollow glass microspheres is soda lime borosilicate, which is a white, micron-sized, hollow spherical glassy light powder material with a smooth surface and good fluidity and sound insulation and noise reduction properties.
[0017] Furthermore, the wood fiber is an organic flocculent fiber material with a small specific gravity, excellent sound insulation and heat insulation properties, which can prevent the coating from cracking and enhance the adhesion of the coating surface.
[0018] Furthermore, the modified bentonite has excellent respiration and atomization effects, and can adjust the drying speed of the sound insulation coating; it also has excellent anti-sagging and anti-suspension properties, which is beneficial to improving construction properties and storage properties.
[0019] Furthermore, the auxiliary agent is selected from one or more of a dispersant, a wetting agent, a mineral oil defoamer, a film-forming aid, a pH adjuster, a polyurethane thickener, a silicone defoamer, a freeze-thaw wetting agent, and a preservative.
[0020] Furthermore, the dispersant has super strong dispersing ability, excellent stability and water resistance.
[0021] Furthermore, the dispersant is selected from ROSF-1023 of Rosif Technology Co., Ltd.
[0022] Furthermore, the wetting agent is selected from BD-109 of Dow Chemical.
[0023] Furthermore, the mineral oil defoamer is selected from DF-1390 of Puwei (Shanghai) New Material Technology Co., Ltd.
[0024] Furthermore, the film-forming aid is selected from Eastman's alcohol ester dodecahydrate.
[0025] Furthermore, the pH regulator is selected from one or more of 2-butylaminoethanol and 2-amino-2-methyl-1-propanol.
[0026] Furthermore, the polyurethane thickener is selected from water-based non-ionic associative hydrophobically modified polyurethane.
[0027] Furthermore, the polyurethane thickener has excellent compatibility, thickening and leveling properties, and water and alkali resistance.
[0028] Furthermore, the organosilicon defoamer is selected from 2410AC of BASF Chemicals.
[0029] Furthermore, the freeze-thaw wetting agent has excellent freeze-thaw resistance, good environmental performance and chemical stability.
[0030] Furthermore, the freeze-thaw wetting agent is selected from PEG300 of Petronas.
[0031] Furthermore, the preservative is selected from one or two of benzisothiazolinone, iodopropynyl n-butylcarbamate, or methylisothiazolinone.
[0032] Another object of the present invention is to provide a method for preparing the above-mentioned lightweight environmentally friendly sound insulation coating with high adhesion and high water resistance, the method for preparing the lightweight environmentally friendly sound insulation coating with high adhesion and high water resistance comprising the following steps:
[0033] S1, add an emulsifier into a container, dropwise add an organosiloxane and an organosilicon coupling agent, heat at 70-90°C for reaction, dropwise add acrylate to continue the reaction, and obtain an organosilicon-modified acrylic emulsion;
[0034] S2, blending and stirring the dispersant, wetting agent, pH adjuster, and silica aerogel powder, adding a defoamer and stirring to obtain an aerogel dispersion slurry;
[0035] S3, blending bentonite and acrylate, heating at 190-210°C to react, to obtain acrylate-grafted bentonite; blending hollow glass microspheres and silane coupling agent, heating at 55-65°C to react, to obtain silane coupling agent-grafted hollow glass microspheres; blending wood fiber and eleostearic acid, heating at 50-100°C to react, to obtain eleostearic acid-grafted wood fiber;
[0036] S4, under an inert atmosphere, blending acrylate grafted bentonite, silane coupling agent grafted hollow glass microspheres, and eleostearic acid grafted wood fiber, heating and reacting to obtain modified bentonite;
[0037] S5. Blend the organosilicon-modified acrylic emulsion, aerogel dispersion slurry, modified bentonite and other components, and stir to obtain a lightweight, environmentally friendly sound insulation coating with high adhesion and high water resistance.
[0038] Furthermore, in step S1, the mass ratio of the organosiloxane, the organosilicon coupling agent, and the acrylate is (20-40):(2-7):(1-5).
[0039] Furthermore, in step S2, the mass ratio of the dispersant, wetting agent, pH regulator, aerogel powder and defoaming agent is 3:2:0.5:(30-40):(1-5).
[0040] Furthermore, in step S3, the mass ratio of bentonite to acrylate is 1:(45-55); the mass ratio of hollow glass microspheres to silane coupling agent is 1:(0.2-0.4); and the amount of eleostearic acid is 1-5 times the amount of active hydroxyl substances in wood fiber.
[0041] Furthermore, in step S4, the mass ratio of the acrylate grafted bentonite, the silane coupling agent grafted hollow glass microspheres, and the eleostearic acid grafted wood fiber is (1-3):(1-3):(1-3).
[0042] The present invention has the following beneficial effects:
[0043] The light and environmentally friendly sound insulation coating with high adhesion and high water resistance provided by the present invention is added with modified bentonite. On the one hand, it has a certain thickening effect, replacing the existing product by adding hydroxyethyl cellulose for thickening, and can improve the drying speed, water resistance, storage and construction properties of the sound insulation coating. In addition, it is matched with a polyurethane thickener, and the synergistic effect of the two further improves the water resistance of the sound insulation coating, solves the problems of poor storage, slow drying after application and poor construction experience of the existing sound insulation coating, and further improves the water resistance of the product and the durability of the coating; on the other hand, the modified bentonite is prepared by polymerization of acrylate grafted bentonite, silane coupling agent grafted hollow glass microspheres, and eleostearic acid grafted wood fiber, thereby introducing acrylate groups, hollow glass microsphere particles and wood fiber particles, enhancing the compatibility of the components, and enabling components such as silicone-modified acrylic emulsion, hollow glass microspheres, and wood fibers to be more evenly dispersed to avoid agglomeration, thereby improving the adhesion, water resistance, sound insulation and other performances of the coating.
[0044] The present invention also adds an organosilicon-modified acrylic emulsion as a main film-forming substance. The emulsion has the characteristics of a high organosilicon modification amount, and the organosilicon content reaches 30-40%, which can significantly improve the water resistance and bonding strength of the emulsion, enhance the water resistance and bonding strength of the coating film, and can firmly attach the sound insulation coating to the surface of the substrate. In addition, the modified emulsion also has excellent flexibility and crack resistance, and the protective coating does not crack when thickly applied, which effectively solves the problem that the existing products are easy to crack when thickly applied, and have poor bonding strength and water resistance.
[0045] The present invention also uses silica aerogel, expanded perlite, hollow glass microspheres and wood fiber as sound insulation fillers, giving the coating the characteristics of light weight, environmental protection and excellent sound insulation effect. Wood fiber not only has the characteristic of preventing the coating from cracking, but also can play a synergistic role with silicone-modified acrylic emulsion to further enhance the thick coating crack resistance and improve the durability of the coating. At the same time, through the preferred process, the silica aerogel is first prepared into a silica aerogel dispersion slurry with a solid content of 30% by a high-speed stirring method, and then added to the finished product for dispersion, which solves the problem of poor dispersibility of the silica aerogel.
[0046] In addition, the lightweight and environmentally friendly sound insulation coating of the present invention also adds a special freeze-thaw wetting agent, so there is no need to add any additional alcohol ether additives to provide antifreeze effect. It can not only make the product have less odor, lower VOC, and better environmental protection, but also further accelerate the drying speed of the product under thick coating, solving the existing technical problems. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 The preparation principle of the coating of Example 1 is shown, wherein the sound insulation filler includes silica aerogel, expanded perlite, hollow glass microspheres and wood fiber. DETAILED DESCRIPTION
[0048] In order to more clearly illustrate the technical solution of the present invention, the following examples are listed. Unless otherwise stated, the raw materials, reactions and post-treatment methods shown in the examples are common raw materials on the market and technical methods well known to those skilled in the art.
[0049] The words "preferred", "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0050] It should be understood that, except in any operating examples, or where otherwise indicated, all numbers indicating, for example, the amounts of ingredients used in the specification and claims should be understood to be modified in all cases by the term "about". Therefore, unless indicated to the contrary, the numerical parameters set forth in the following specification and the appended claims are approximate values that vary depending on the desired properties to be obtained by the present invention.
[0051] The following raw materials are used in the embodiments of the present invention:
[0052] Dodecylbenzenesulfonic acid, emulsifier, was purchased from Zhejiang Mingxiang Organic Additives Company;
[0053] Octamethylcyclotetrasiloxane, an organosiloxane monomer, was purchased from Zhejiang Mingxiang Organic Additives Company;
[0054] γ-Methacryloxypropylmethyltrioxysilane, an organosilicon coupling monomer, was purchased from Zhejiang Mingxiang Organic Additives Company;
[0055] Methyl methacrylate, an acrylate monomer, was purchased from Zhejiang Mingxiang Organic Additives Company;
[0056] AMP-95, pH adjuster;
[0057] P30, dispersant, purchased from Coatex, France;
[0058] LCN070, wetting agent, purchased from Clariant Chemicals;
[0059] KNF-W20-H, hydrophobic aerogel powder, purchased from Anhui Keang Company;
[0060] Expanded perlite, particle size 2-4mm;
[0061] Hollow glass microspheres, particle size 50-150μm;
[0062] RM-8W, polyurethane thickener, purchased from The Dow Chemical Company;
[0063] 2410AC, silicone defoamer, purchased from BASF Chemical Company;
[0064] DF-1390, mineral oil defoamer, purchased from Puwei (Shanghai) New Material Technology Co., Ltd.;
[0065] PEG 300, a freeze-thaw wetting agent, was purchased from Petronas;
[0066] MBS5050, preservative, purchased from Thor Chemical Group;
[0067] Wood fiber was purchased from Riedenmeier, Germany.
[0068] Example 1
[0069] A lightweight, environmentally friendly sound-insulating coating with high adhesion and water resistance, comprising the following components in parts by mass:
[0070]
[0071] The preparation method of the lightweight environmentally friendly sound insulation coating with high adhesion and high water resistance comprises the following steps:
[0072] S1, dissolving 3.2 parts of dodecylbenzenesulfonic acid in 50 parts of deionized water, then transferring to a four-necked flask with a mechanical stirrer and a condenser, heating to 80°C under continuous stirring, adding 35 parts of octamethylcyclotetrasiloxane and 5 parts of γ-methacryloxypropylmethyltrioxysilane dropwise within 1 hour, reacting for 12 hours, cooling to 40°C, adjusting the pH value to 7-8 with 0.5 parts of AMP-95, heating to 80°C, adding 1.2 parts of methyl methacrylate and 0.3 parts of ammonium persulfate dropwise within 2 hours, keeping warm for 4 hours, cooling to room temperature, adjusting the pH with 0.5 parts of AMP-95, filtering, discharging, and obtaining the organosilicon-modified acrylic emulsion;
[0073] S2, add 64 parts of water to a stirring container, slowly add 3 parts of P30, 2 parts of LCN070 and 0.5 parts of AMP-95 under low-speed stirring, stir until dispersed evenly, and fully dissolved in water; slowly add 30 parts of KNF-W20-H, increase the speed to 1200-1500 rpm, and stir at high speed for 20 minutes to ensure that KNF-W20-H is fully dispersed; finally, add 3 parts of 2410AC, stir at medium speed until dispersed evenly, and obtain the aerogel dispersion slurry;
[0074] S3. Mix bentonite, potassium persulfate, propyl acrylate and solvent ethanol (the mass ratio of bentonite, potassium persulfate, propyl acrylate and solvent is 1:1.5:50:70) to obtain a suspension solution, add deionized water of the same mass as the suspension solution, heat to 200°C and stir for 0.5h, wait until the suspension solution is evenly dispersed, continue heating and reacting for 5h, filter, put into an oven at 90°C and dry for 3h to obtain propyl acrylate grafted bentonite; add hollow glass microspheres and KH570 to a 90% ethanol aqueous solution (the mass ratio of hollow glass microspheres, KH570 and ethanol is 1:0.2:20), disperse by ultrasonic at 60°C for 1h, filter and dry. , grinding, and sieving to obtain hollow glass microspheres grafted with a silane coupling agent; blending wood fiber, anhydrous pyridine, and 2 parts of elaeolic acid chloride of active hydroxyl groups of wood fiber, adding catalyst N,N-dimethylaminopyridine (the mass ratio of wood fiber, anhydrous pyridine, and N,N-dimethylaminopyridine is 1:30:0.05), heating to 50°C for reaction for 6 hours, and then adding 50% ethanol aqueous solution (the mass ratio of wood fiber to ethanol is 1:20) and stirring for 30 minutes, filtering, washing three times with a small amount of ethanol, and then washing once with acetone, extracting with acetone in a Soxhlet extractor for 16 hours, and then drying in an oven at 60°C for 24 hours to obtain elaeolic acid grafted wood fiber;
[0075] S4. Under a nitrogen environment, add sodium ethylenediamine sulfonate, propyl acrylate grafted bentonite, silane coupling agent grafted hollow glass microspheres, eleostearic acid grafted wood fiber into deionized water (the mass ratio of sodium ethylenediamine sulfonate, propyl acrylate grafted bentonite, silane coupling agent grafted hollow glass microspheres, eleostearic acid grafted wood fiber, and deionized water is 0.2:1:1:1:10) and stir for 15 minutes, heat to 80°C, add ammonium persulfate dropwise (the mass ratio of propyl acrylate grafted bentonite and ammonium persulfate is 1:0.1), react for 3 hours, filter, and dry to obtain modified bentonite;
[0076] S5. According to the above mass fractions, water, silicone-modified acrylic emulsion and hydroxyethyl cellulose are blended, mechanically stirred at a speed of 200 r / min for 5 minutes until completely dissolved, and then 0.6 parts of P30, 0.4 parts of LCN070, 0.3 parts of DF-1390, 2.5 parts of alcohol ester twelve and 0.1 parts of AMP-95 are added in sequence, the speed is increased to 500 r / min and stirring is continued for 4 minutes, and then aerogel dispersion slurry, expanded perlite, hollow glass microspheres, wood fiber and modified bentonite are added in sequence while maintaining the speed of 500 r / min, the speed is increased to 800 r / min and stirred for 20 minutes, and after reducing the speed to 600 r / min, 0.4 parts of RM-8W, 0.3 parts of 2410AC, 1.3 parts of PEG 300 and 0.1 parts of MBS5050 are added in sequence, and stirring is continued for 8 minutes until uniformly dispersed to obtain a lightweight, environmentally friendly sound insulation coating with high adhesion and high water resistance.
[0077] Figure 1 The preparation principle of the coating of Example 1 is shown.
[0078] Example 2
[0079] A lightweight, environmentally friendly sound-insulating coating with high adhesion and water resistance, comprising the following components in parts by mass:
[0080]
[0081] The preparation method of the lightweight environmentally friendly sound insulation coating with high adhesion and high water resistance comprises the following steps:
[0082] S1, dissolving 3.2 parts of dodecylbenzenesulfonic acid in 50 parts of deionized water, and then transferring to a 250 ml four-necked flask with a mechanical stirrer and a condenser, heating to 80° C. under continuous stirring, adding 35 parts of octamethylcyclotetrasiloxane and 5 parts of γ-methacryloxypropylmethyltrioxysilane dropwise within 1 hour, reacting for 12 hours, cooling to 40° C., adjusting the pH value to 7-8 with 0.5 parts of AMP-95, heating to 80° C., adding 1.2 parts of methyl methacrylate and 0.3 parts of ammonium persulfate dropwise within 2 hours, keeping warm for 4 hours, cooling to room temperature, adjusting the pH value with 0.5 parts of AMP-95, filtering, discharging, and obtaining the organosilicon-modified acrylic emulsion;
[0083] S2, add 64 parts of water to a stirring container, slowly add 3 parts of P30, 2 parts of LCN070 and 0.5 parts of AMP-95 under low-speed stirring, stir until dispersed evenly, and fully dissolved in water; slowly add 30 parts of KNF-W20-H, increase the speed to 1200-1500 rpm, and stir at high speed for 20 minutes to ensure that KNF-W20-H is fully dispersed; finally, add 3 parts of 2410AC, stir at medium speed until dispersed evenly, and obtain the aerogel dispersion slurry;
[0084] S3. Mix bentonite, potassium persulfate, propyl acrylate and solvent ethanol (the mass ratio of bentonite, potassium persulfate, propyl acrylate and solvent is 1:1.5:50:70) to obtain a suspension solution, add deionized water of the same mass as the suspension solution, heat to 200°C and stir for 0.5h, wait until the suspension solution is evenly dispersed, continue heating and reacting for 5h, filter, put into an oven at 90°C and dry for 3h to obtain propyl acrylate grafted bentonite; add hollow glass microspheres and KH570 to a 90% ethanol aqueous solution (the mass ratio of hollow glass microspheres, KH570 and ethanol is 1:0.2:20), disperse by ultrasonic at 60°C for 1h, filter and dry. , grinding, and sieving to obtain hollow glass microspheres grafted with a silane coupling agent; blending wood fiber, anhydrous pyridine, and 2 parts of elaeolic acid chloride of active hydroxyl groups of wood fiber, adding catalyst N,N-dimethylaminopyridine (the mass ratio of wood fiber, anhydrous pyridine, and N,N-dimethylaminopyridine is 1:30:0.05), heating to 50°C for reaction for 6 hours, and then adding 50% ethanol aqueous solution (the mass ratio of wood fiber to ethanol is 1:20) and stirring for 30 minutes, filtering, washing three times with a small amount of ethanol, and then washing once with acetone, extracting with acetone in a Soxhlet extractor for 16 hours, and then drying in an oven at 60°C for 24 hours to obtain elaeolic acid grafted wood fiber;
[0085] S4. Under a nitrogen environment, add sodium ethylenediamine sulfonate, propyl acrylate grafted bentonite, silane coupling agent grafted hollow glass microspheres, eleostearic acid grafted wood fiber into deionized water (the mass ratio of sodium ethylenediamine sulfonate, propyl acrylate grafted bentonite, silane coupling agent grafted hollow glass microspheres, eleostearic acid grafted wood fiber, and deionized water is 0.2:1:1:1:10) and stir for 15 minutes, heat to 80°C, add ammonium persulfate dropwise (the mass ratio of propyl acrylate grafted bentonite and ammonium persulfate is 1:0.1), react for 3 hours, filter, and dry to obtain modified bentonite;
[0086] S5. According to the above mass fractions, water, silicone-modified acrylic emulsion and hydroxyethyl cellulose are blended, mechanically stirred at a speed of 500 r / min for 10 minutes until completely dissolved, and then 1.0 parts of P30, 0.2 parts of LCN070, 0.5 parts of DF-1390, 2.1 parts of alcohol ester twelve and 0.2 parts of AMP-95 are added in sequence, the speed is increased to 800 r / min and stirring is continued for 4 minutes, and then aerogel dispersion slurry, expanded perlite, hollow glass microspheres, wood fiber and modified bentonite are added in sequence while maintaining the speed of 800 r / min, the speed is increased to 1000 r / min and stirred for 15 minutes, and after reducing the speed to 800 r / min, 0.2 parts of RM-8W, 0.2 parts of 2410AC, 1.0 parts of PEG 300 and 0.3 parts of MBS5050 are added in sequence, and stirring is continued for 5 minutes until uniformly dispersed to obtain a lightweight, environmentally friendly sound insulation coating with high adhesion and high water resistance.
[0087] Example 3
[0088] A lightweight, environmentally friendly sound-insulating coating with high adhesion and water resistance, comprising the following components in parts by mass:
[0089] 28 parts of silicone modified acrylic emulsion
[0090]
[0091] The preparation method of the lightweight environmentally friendly sound insulation coating with high adhesion and high water resistance comprises the following steps:
[0092] S1, dissolving 3.2 parts of dodecylbenzenesulfonic acid in 50 parts of deionized water, and then transferring to a 250 ml four-necked flask with a mechanical stirrer and a condenser, heating to 80° C. under continuous stirring, adding 35 parts of octamethylcyclotetrasiloxane and 5 parts of γ-methacryloxypropylmethyltrioxysilane dropwise within 1 hour, reacting for 12 hours, cooling to 40° C., adjusting the pH value to 7-8 with 0.5 parts of AMP-95, heating to 80° C., adding 1.2 parts of methyl methacrylate and 0.3 parts of ammonium persulfate dropwise within 2 hours, keeping warm for 4 hours, cooling to room temperature, adjusting the pH value with 0.5 parts of AMP-95, filtering, discharging, and obtaining the organosilicon-modified acrylic emulsion;
[0093] S2, add 64 parts of water to a stirring container, slowly add 3 parts of P30, 2 parts of LCN070 and 0.5 parts of AMP-95 under low-speed stirring, stir until dispersed evenly, and fully dissolved in water; slowly add 30 parts of KNF-W20-H, increase the speed to 1200-1500 rpm, and stir at high speed for 20 minutes to ensure that KNF-W20-H is fully dispersed; finally, add 3 parts of 2410AC, stir at medium speed until dispersed evenly, and obtain the aerogel dispersion slurry;
[0094] S3. Mix bentonite, potassium persulfate, propyl acrylate and solvent ethanol (the mass ratio of bentonite, potassium persulfate, propyl acrylate and solvent is 1:1.5:50:70) to obtain a suspension solution, add deionized water of the same mass as the suspension solution, heat to 200°C and stir for 0.5h, wait until the suspension solution is evenly dispersed, continue heating and reacting for 5h, filter, put into an oven at 90°C and dry for 3h to obtain propyl acrylate grafted bentonite; add hollow glass microspheres and KH570 to a 90% ethanol aqueous solution (the mass ratio of hollow glass microspheres, KH570 and ethanol is 1:0.2:20), disperse by ultrasonic at 60°C for 1h, filter and dry. , grinding, and sieving to obtain hollow glass microspheres grafted with a silane coupling agent; blending wood fiber, anhydrous pyridine, and 2 parts of elaeolic acid chloride of active hydroxyl groups of wood fiber, adding catalyst N,N-dimethylaminopyridine (the mass ratio of wood fiber, anhydrous pyridine, and N,N-dimethylaminopyridine is 1:30:0.05), heating to 50°C for reaction for 6 hours, and then adding 50% ethanol aqueous solution (the mass ratio of wood fiber to ethanol is 1:20) and stirring for 30 minutes, filtering, washing three times with a small amount of ethanol, and then washing once with acetone, extracting with acetone in a Soxhlet extractor for 16 hours, and then drying in an oven at 60°C for 24 hours to obtain elaeolic acid grafted wood fiber;
[0095] S4. Under a nitrogen environment, add sodium ethylenediamine sulfonate, propyl acrylate grafted bentonite, silane coupling agent grafted hollow glass microspheres, eleostearic acid grafted wood fiber into deionized water (the mass ratio of sodium ethylenediamine sulfonate, propyl acrylate grafted bentonite, silane coupling agent grafted hollow glass microspheres, eleostearic acid grafted wood fiber, and deionized water is 0.2:1:1:1:10) and stir for 15 minutes, heat to 80°C, add ammonium persulfate dropwise (the mass ratio of propyl acrylate grafted bentonite and ammonium persulfate is 1:0.1), react for 3 hours, filter, and dry to obtain modified bentonite;
[0096] S5. According to the above mass fractions, water, silicone-modified acrylic emulsion and hydroxyethyl cellulose are blended, mechanically stirred at a speed of 350 / min for 7.5 minutes until completely dissolved, and then 0.8 parts of P30, 0.3 parts of LCN070, 0.4 parts of DF-1390, 2.3 parts of alcohol ester twelve and 0.15 parts of AMP-95 are added in sequence, the speed is increased to 650r / min and stirring is continued for 5 minutes, and then aerogel dispersion slurry, expanded perlite, hollow glass microspheres, wood fiber and modified bentonite are added in sequence while maintaining the speed of 650r / min, the speed is increased to 900r / min and stirred for 17.5 minutes, and after reducing the speed to 700r / min, 0.3 parts of RM-8W, 0.25 parts of 2410AC, 1.15 parts of PEG 300 and 0.2 parts of MBS5050 are added in sequence, and stirring is continued for 6.5 minutes until uniformly dispersed to obtain a lightweight, environmentally friendly sound insulation coating with high adhesion and high water resistance.
[0097] Comparative Example 1
[0098] The difference between Comparative Example 1 and Example 1 is that the silicone-modified acrylic emulsion is replaced by an equal mass of a commonly used silicone-acrylic emulsion (brand name BADF 996AD) on the market, step S1 is deleted, and the other components, mass fractions and preparation methods remain unchanged.
[0099] Comparative Example 2
[0100] The difference between Comparative Example 2 and Example 1 is that step S2 is deleted, the aerogel dispersion slurry is replaced by an equal mass of KNF-W20-H, and the other components, mass fractions and preparation methods remain unchanged.
[0101] Comparative Example 3
[0102] The difference between Comparative Example 3 and Example 1 is that the part of preparing eleostearic acid grafted wood fiber in step S3 is deleted, eleostearic acid grafted wood fiber is not added in step S4, and the other components, mass fractions and preparation methods remain unchanged.
[0103] Comparative Example 4
[0104] Comparative Example 4 is a sound insulation coating product of the prior art, and its ingredients are as follows: 11 parts of styrene acrylic emulsion, 0.6 parts of hydroxyethyl cellulose, 0.8 parts of film-forming aid, 0.2 parts of defoaming agent, 0.5 parts of bactericide, 0.1 parts of pH adjuster, 0.8 parts of ethylene glycol, 44 parts of 70 mesh snow white, 6 parts of rubber, 6 parts of mineral fiber cotton, 0.5 parts of thickener, and 30 parts of water.
[0105] Test Example 1
[0106] The coating construction performance, drying time (surface drying), initial drying crack resistance (3 mm thick), water resistance and heat storage (15 d), bonding strength, sound insulation, and VOC content of Examples 1-3 and Comparative Examples 1-4 were tested.
[0107] Test Method
[0108] The coating construction performance, drying time (surface drying), initial drying crack resistance (3mm thickness), water resistance and thermal storage (15d) are tested in accordance with the provisions of JG / T24-2018 standard. The calculation method for the weight of the 5mm sprayed coating per square meter is to calculate the weight of the coating based on the coating thickness and the density of the coating; the bonding strength is tested according to 7.6 in GB / T 23445-2009 for the results after untreated and immersion treatment; the test method for sound insulation performance is to spray the sound insulation coating product on a reinforced concrete floor with a weighted normalized impact sound pressure level of Ln,w=78dB, spray twice, with a thickness of 5mm, and no decorative layer on the surface, and then test according to GB / T 50121-2005 and GB / T 19889.8-2006; VOC content is tested in accordance with GB 18582-2020 standards.
[0109] Test Results
[0110] Table 1 shows the test results of Examples 1-3 and Comparative Examples 1-4
[0111] Table 1 Test results of Examples 1-3 and Comparative Examples 1-4
[0112]
[0113]
[0114] As can be seen from Table 1, Examples 1-3 have good adhesion, water resistance, sound insulation and other properties, and are lightweight and environmentally friendly, which are significantly better than Comparative Examples 1-4. Comparative Example 1 replaces the silicone-modified acrylic emulsion with an equal mass of commonly used silicone-acrylic emulsion (brand name Baderfu 996AD) on the market, which reduces the silicon content in the emulsion, resulting in reduced water resistance, adhesion, and crack resistance. Comparative Example 2 deletes step S2 and replaces the aerogel dispersion slurry with an equal mass of KNF-W20-H, which reduces the dispersibility of the silica aerogel, resulting in reduced sound insulation performance, poor construction performance, and an increase in the weight of a 5mm thick coating sprayed per square meter. Comparative Example 3 replaces the modified bentonite with an equal mass of modified bentonite that does not contain eleostearic acid-grafted wood fiber, which reduces the compatibility of the components, resulting in extended drying time, reduced crack resistance, and reduced sound insulation performance. Comparative Example 4 uses a prior art sound insulation coating product, which does not contain the modified bentonite, silicone-modified acrylic emulsion and other components of the examples, resulting in various performances being lower than those of the examples, and having a higher VOC and less than ideal environmental performance.
[0115] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0116] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A lightweight, environmentally friendly sound-insulating coating with high adhesion and high water resistance, characterized in that: The highly adhesive and water-resistant lightweight environmentally friendly sound-insulating coating comprises the following components in parts by weight: The modified bentonite is obtained by reacting acrylate grafted bentonite, silane coupling agent grafted hollow glass microspheres, and eleostearic acid grafted wood fiber; The organosilicon-modified acrylic emulsion is obtained by the reaction of organosiloxane, organosilicon coupling agent and acrylate.
2. The lightweight, environmentally friendly sound-insulating coating with high adhesion and high water resistance according to claim 1, characterized in that: The particle size of the expanded perlite is 2-4 mm.
3. The lightweight, environmentally friendly sound-insulating coating with high adhesion and high water resistance according to claim 1, characterized in that: The particle size of the hollow glass microspheres is 50-150 μm.
4. The lightweight, environmentally friendly sound-insulating coating with high adhesion and high water resistance according to claim 1, characterized in that: The auxiliary agent is selected from one or more of a dispersant, a wetting agent, a mineral oil defoamer, a film-forming aid, a pH regulator, a polyurethane thickener, a silicone defoamer, a freeze-thaw wetting agent, and a preservative.
5. The method for preparing the lightweight environmentally friendly sound insulation coating with high adhesion and high water resistance according to any one of claims 1 to 4, characterized in that: The method for preparing the lightweight environmentally friendly sound insulation coating with high adhesion and high water resistance comprises the following steps: S1, add an emulsifier into a container, dropwise add an organosiloxane and an organosilicon coupling agent, heat at 70-90°C for reaction, dropwise add acrylate to continue the reaction, and obtain an organosilicon-modified acrylic emulsion; S2, blending and stirring the dispersant, wetting agent, pH adjuster, and silica aerogel powder, adding a defoamer and stirring to obtain an aerogel dispersion slurry; S3, blending bentonite and acrylate, heating at 190-210°C to react, to obtain acrylate-grafted bentonite; blending hollow glass microspheres and silane coupling agent, heating at 55-65°C to react, to obtain silane coupling agent-grafted hollow glass microspheres; blending wood fiber and eleostearic acid, heating at 50-100°C to react, to obtain eleostearic acid-grafted wood fiber; S4, under an inert atmosphere, blending acrylate grafted bentonite, silane coupling agent grafted hollow glass microspheres, and eleostearic acid grafted wood fiber, heating and reacting to obtain modified bentonite; S5. Blend the organosilicon-modified acrylic emulsion, aerogel dispersion slurry, modified bentonite and other components, and stir to obtain a lightweight, environmentally friendly sound insulation coating with high adhesion and high water resistance.
6. The method for preparing the lightweight environmentally friendly sound insulation coating with high adhesion and high water resistance according to claim 5, characterized in that: In step S1, the mass ratio of the organosiloxane, the organosilicon coupling agent and the acrylate is (20-40):(2-7):(1-5).
7. The method for preparing the lightweight environmentally friendly sound insulation coating with high adhesion and high water resistance according to claim 5, characterized in that: In step S2, the mass ratio of the dispersant, wetting agent, pH adjuster, aerogel powder and defoaming agent is 3:2:0.5:(30-40):(1-5).
8. The method for preparing the lightweight, environmentally friendly sound-insulating coating with high adhesion and high water resistance according to claim 5, characterized in that: In step S3, the mass ratio of bentonite to acrylate is 1:(45-55); the mass ratio of hollow glass microspheres to silane coupling agent is 1:(0.2-0.4); and the amount of eleostearic acid is 1-5 times the amount of active hydroxyl substances in wood fiber.
9. The method for preparing the lightweight environmentally friendly sound insulation coating with high adhesion and high water resistance according to claim 5, characterized in that: In step S4, the mass ratio of the acrylate grafted bentonite, the silane coupling agent grafted hollow glass microspheres, and the eleostearic acid grafted wood fiber is (1-3):(1-3):(1-3).
Citation Information
Patent Citations
Manufacture method of eleostearic acid graft modification wood fibers
CN102643439A
Novel thermal-insulation material for boilers and preparation method of novel thermal-insulation material
CN106147137A
Waterproof heat-insulation exterior wall coating and preparation method thereof
CN108329780A
Nano heat insulation coating material
CN109401495A
High-performance sound insulation coating and preparation method thereof
CN116102925A